Current Mood vs. Recalled Impacts of Current Moods after Exposures to Sequences of Uncertain Monetary Outcomes - Olsson, Lars E.; Gärling, Tommy; Ettema, Dick; Friman, Margareta; Ståhl, Michael (Frontiers in Psychology, 2017)
Events in a sequence may each be evaluated as good or bad. We propose that such good-bad evaluations evoke emotional responses that change current mood. A model of recurrent updating of current mood is developed and compared to a model of how a sequence of events evoking emotional responses is evaluated retrospectively. In Experiment 1, 149 undergraduates are presented sequences of lottery outcomes with a fixed probability of losing or winning different amounts of money. Ratings of current mood are made after the sequence. Retrospective evaluations are either made after the ratings of current mood or, in a control condition, when no ratings of current mood are made. The results show an expected effect on current mood of the valence of the end of the sequence. The results are less clear in showing an expected beginning effect on the retrospective evaluations. An expected beginning effect on retrospective evaluations is found in Experiment 2 in which 41 undergraduates are first asked to remember the different amounts of money, then to evaluate the sequence as lottery outcomes.